Modelo de campo de fase para crescimento dendrítico com heterogeneidades - Rodrigues, Francisco Leandro de Oliveira (2017)
In the solidification of a metal, the interface advances anisotropically. This process occurs when a fluid is subcooled below its solidification point, where the nucleated crystal grows without a preferred direction, forming microstructured patterns. This type of phenomenon is called dendritic growth. In this work we show that through the insertion of blocks in the domain sites, with regular and random spacing, this anisotropy is broken. That is, the structure no longer contains its branched structure, tending more and more to a circular structure. We also verified that the dendritic growth structure, without blocks, grows over time according to a second degree polynomial equation. However, by increasing the number of blocks in the domain, this growth tends to follow a first-degree equation, ie, the perimeter starts to grow linearly with time. In addition, in the random blocking process the solidification seed stops growing in time, in which case it does not occur in regular blocking.